Spatial coding for action across spatial scales - Fiehler, Katja; Karimpur, Harun; Justus Liebig University Giessen (My University, 2023)
Humans perform goal-directed actions such as reaching for a light switch or grasping a coffee mug thousands of times a day. Behind the scenes of these seemingly simple actions, the brain performs sophisticated calculations to locate the target object of the action and correctly guide the hand towards it. In this Review, we discuss how the brain establishes spatial representations used for visually guided actions. In addition to reviewing simple tasks and paradigms, we discuss spatial coding in complex and naturalistic environments. We highlight the importance of high-level cognitive factors, such as memory, task constraints, and object semantics, which influence the use of spatial representations for action. To move the field forward, we suggest that future research should integrate across different scales of action spaces from small-scale finger movements to large-scale navigation. Doing so would enable the identification of general mechanisms that underlie spatial coding across different actions and spaces.
Keywords: space perception; perception and action; spatial reference frames; natural behavior; virtual reality; ddc:150